Kinematic assessment of the NOCSAE headform during blunt impacts with a pneumatic linear impactor - Edwards, E. D.; Landry, T.; Jesunathadas, M.; Plaisted, T. A.; Neice, R. J.; Gould, T. E.; Kleinberger, M.; Piland, S. G. (Sports Engineering, 2023)
The purpose of this study is to explore the bilateral kinematic patterns across the posterior aspect of the medium National Operating Committee on Standards for Athletic Equipment anthropomorphic test device headform during blunt impacts. Such information is important for interpreting and properly deriving blunt impact performance metrics. Two medium National Operating Committee on Standards for Athletic Equipment headforms modified according to National Operating Committee on Standards for Athletic Equipment document ND-081 were attached to a male 50th percentile Hybrid III neck and were impacted at 14 locations along the posterior aspect of the headform (7 ear side, 7 non-ear side). Impacts were performed on a pneumatic linear impactor at 2, 3, and 4 m/s using the impactor head specified by the Standard Pneumatic Ram Test Method Document 081-18am. The peak linear acceleration, peak angular acceleration, and peak angular velocity values were quantified for each impact. The results indicate that peak linear acceleration seems to be consistent, peak angular acceleration is markedly less at the nape and rear regions, whereas peak angular velocity is greatest at the nape and rear regions. Additionally, there are numerous instances where the values between impacts to the ear side of the headform differ from impacts to the non-ear side according to our type-I error rate (alpha = 0.05). Our results provide an indication that there is a large variation in peak angular acceleration at different impact sites across the headform compared to little variation in peak linear and peak angular velocity. Additionally, there are some asymmetries present in the headform that may have clinical relevance for peak linear accelerations and peak angular accelerations, but not for peak angular velocity in the range of values we observed in this study.